(untitled) (The International Journal of Educational Sciences and Arts, 2024)
The study aims to explain the role of information management in achieving comprehensive quality in government organizations through an applied study on the Chamber of Commerce in Jeddah Governorate. The study relied on the descriptive analytical approach because it is the most appropriate scientific research method to describe the role of data management in applying comprehensive quality standards and analyzing the information that is provided. Obtaining it, the questionnaire was used as a tool to collect information from the study population, and the study sample amounted to (72) participants. The study concluded that the level of application of comprehensive quality standards in the Jeddah Chamber of Commerce reached a record level, through continuous improvement, measuring the level of commitment of all departments to applying these standards and periodic follow-up, and sustainable work to make the most of information management and its continuous development in order to keep pace with the modern changes that Ensuring improvement of the Chamber of Commerce’s performance and achieving the best targeted results. The study recommended holding seminars and conferences to increase awareness of the importance of information management to apply comprehensive quality standards, to improve the level of products and services to increase the competitive advantages of local organizations.